An Appraisal of Examination Malpractice in the Perspectives of Islamic Thought - ISA, Sa'idu (Ilorin Journal of Education, 2024)
Examination is conducted to ascertain the comprehension level of a learner; hence it assists a tutor or an institution to determine the knowledge acquired by the learner for certification or scaling to the next level of scholarship. The process is, therefore, guided by defined extant laws. Law and order are part of the major principles of the religion of Islam; thus, the religion attaches special importance to strict observance and adherence to laws. This is because Islamic Thought is built on the oneness of Allah and obedience to divine laws, as contained in the Holy Qur’an and authentic Traditions (Sunnah) of the Prophet of Islam, Muhammad (pbuh). Therefore, this paper examines the stance of Islam on examination malpractice. Documentary Analysis and Survey Research were used as the methods of data collection. The data collected from the Holy Qur’an, the authentic Sunnah of the Prophet Muhammad (pbuh) and the Fatwaa (understanding) of prominent Islamic scholars revealed that Islam has forbidden Muslims from engaging in acts of cheating, breach of trust and anything dishonourable. Since examination malpractice, according to the consensus of Islamic scholars, is an act of cheating, Islam therefore abhors it. Examination malpractice distorts the process of evaluating the methods of instruction to ascertain their effectiveness or otherwise. It has major negative impacts on the development and growth of any state. The paper therefore recommended, among others, the full implementation of the provisions made by the Nigerian constitution on those that engage in examination malpractice to serve as deterrence to students, teachers and other stakeholders in the education sector.